Cocos (Keeling) Corals Reveal 200 Years of Multidecadal Modulation of Southeast Indian Ocean Hydrology by Indonesian Throughflow - Hennekam, R.; Zinke, Jens; van Sebille, E.; ten Have, M.; Brummer, G.; Reichart, G. (2018)
The only low latitude pathway of heat and salt from the Pacific Ocean to the Indian Ocean, known as Indonesian Throughflow (ITF), has been suggested to modulate Global Mean Surface Temperature (GMST) warming through redistribution of surface Pacific Ocean heat. ITF observations are only available since ~1990s, and thus, its multidecadal variability on longer time scales has remained elusive. Here we present a 200 year bimonthly record of geochemical parameters (d 18 O-Sr/Ca) measured on Cocos (Keeling) corals tracking sea surface temperature (SST; Sr/Ca) and sea surface salinity (SSS; seawater-d 18 O-d 18 O sw ) in the southeastern tropical Indian Ocean (SETIO). Our results show that SETIO SSS and d 18 O sw were impacted by ITF transport over the past 60 years, and therefore, reconstructions of Cocos d 18 O sw hold information on past ITF variability on longer time spans. Over the past 200 years ITF leakage into SETIO is dominated by the interannual climate modes of the Pacific Ocean (El Niño—Southern Oscillation) and Indian Ocean (Indian Ocean Dipole). Pacific decadal climate variability (represented by the Pacific Decadal Oscillation) significantly impacted ITF strength over the past 200 years determining the spatiotemporal SST and SSS advection into the Indian Ocean on multidecadal time scales. A comparison of our SETIO d 18 O sw record to GMST shows that ITF transport varied in synchrony with global warming rate, being predominantly high/low during GMST warming slowdown/acceleration, respectively. This hints toward an important role for the ITF in global warming rate modulation.